COMPLICATIONS OF OPENING WEDGE HIGH TIBIAL OSTEOTOMY - V. E. Byalik; S. A. Makarov; L. I. Alekseeva; E. I. Byalik; S. V. Arkhipov; S. I. Glukhova; M. R. Nurmukhametov; V. A. Nesterenko (Научно-практическая ревматология)
Opening wedge high tibial osteotomy (OWHTO) is a surgical treatment option for osteoarthritis (OA) of the knee with a predominant lesion of its medial segment, which can restore the mechanical axis of the lower limb, transfer load from affected medial to intact lateral part of knee joint, and thus slow OA progression, reduce or even abolish pain, prolong the function of the patient’s own knee joint, and delay total knee arthroplasty. Like any surgical intervention, OWHTO can be responsible for common, local, and specific surgical complicationsObjective: to investigate complications from OWHTO and to determine the impact of the design of short spacer plates, bone graft materials and/or bone substitutes, as well as age, body weight and wedge angle correction on the development of complications in patients undergoing this surgery.Subjects and methods. Twenty-eight OWHTOs were performed in 26 patients in 2003 to 2016. The male and female ratio was approximately 2:1. The patients’ mean age was 58.1±11.24 years; body mass index, 28.56±3.61 kg/m2; correction angle, 11.8±2.4°. Fixation was carried out using short spacer plates of three different designs: Puddu plate I, II, and Osteomed. Bone grafting was performed applying an iliac wing autograft or a biodegradable bone substitute (β-tricalcium phosphate) as rectangular blocks, or Inject. Bone grafting was not done when the wedge size was <10 mm.Results and discussion. Twelve complications were diagnosed in 11 of the 28 (39.25%) cases. Of these, there were 8 cases of pain at the site of the implanted plate, three intra-articular fractures of the lateral tibial plateau, and one case of impaired polymerization of liquid β-tricalcium phosphate. There were no statistically significant relationships between the parameters investigated and the development of complications.Conclusion. Clamp-associated complications develop with the same frequency regardless of the design of short spacer plates. The use of liquid β-tricalcium phosphate should be avoided in closing wedge osteotomy. Age, body weight, and the magnitude of a correction angle are unassociated with the development of complications in OWHTO.